2022
DOI: 10.3389/fphar.2022.953982
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes as bacterial efflux pump inhibitors: A systematic review

Abstract: Managing antibiotic resistance is a significant challenge in modern pharmacotherapy. While molecular analyses have identified efflux pump expression as an essential mechanism underlying multidrug resistance, the targeted drug development has occurred slower. Thus, considering the verification that terpenes can enhance the activity of antibiotics against resistant bacteria, the present study gathered evidence pointing to these natural compounds as bacterial efflux pump inhibitors. A systematic search for manusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…One of the notable properties of terpenes is their antibacterial activity. While the specific mechanisms of action may vary depending on the terpene and the bacterial species, some common mechanisms include disruption of cell membranes, inhibition of enzyme activity, and interference with bacterial growth and replication [ 148 , 149 , 150 , 151 ]. Recently, terpenes have been found to be effective inhibitors of efflux pumps in a diverse range of bacterial strains, suggesting their potential utility in drug development for addressing antibiotic resistance [ 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the notable properties of terpenes is their antibacterial activity. While the specific mechanisms of action may vary depending on the terpene and the bacterial species, some common mechanisms include disruption of cell membranes, inhibition of enzyme activity, and interference with bacterial growth and replication [ 148 , 149 , 150 , 151 ]. Recently, terpenes have been found to be effective inhibitors of efflux pumps in a diverse range of bacterial strains, suggesting their potential utility in drug development for addressing antibiotic resistance [ 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies investigating interactions between EOCs and conventional antibiotics against Gram-negative bacteria and fungi. Much of the focus has shifted to investigating how EOCs can attenuate virulence factors and resistance mechanisms [ 23 , 25 , 26 ]. Based on current therapies, many existing antibiotic strategies rely on combinations of an antibiotic with an adjuvant to target a resistance mechanism and “resensitize” the micro-organism to the antibiotic [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…These essential oil compounds (EOCs) are responsible for the pharmacological properties of an EO and, more specifically, their antimicrobial properties [ 24 ]. EOCs have been studied independently and are actively being sought as novel chemical entities for antimicrobial development [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…to control the growth of crop-related disease causal agents (reviewed by Raveau, et al [31]). Accordingly, the leaves of E. globulus are characteristically rich in terpenes, flavonoids, and phenolic acids, whose antibacterial activities have already been described [28,32,33], and for that reason, eucalyptus leaf extracts can constitute a great antimicrobial strategy. As a matter of fact, a previous study has reported strong inhibitory properties of E. globulus extracts against human-pathogen bacteria, such as P. aeruginosa [24].…”
Section: Discussionmentioning
confidence: 99%